2023
DOI: 10.1186/s12941-023-00627-6
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis on the mutations associated with multidrug-resistant urogenital mycoplasmas and ureaplasmas infection: a systematic review and meta-analysis

Abstract: Background The emergence of multidrug-resistant (MDR) strains of genital pathogens, notably Mycoplasma genitalium and Ureaplasma spp., constitutes a significant global threat today. The present study aimed to evaluate the prevalence and trend of changes in MDR mycoplasma and ureaplasma strains. Methods An exhaustive search was performed across the ISI Web of Science, PubMed, Scopus, ScienceDirect, and Google Scholar databases to accumulate relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 89 publications
1
0
0
Order By: Relevance
“…While fluoroquinolone resistance may not always lead to treatment failure, certain patients may still respond favourably to moxifloxacin treatment. Nevertheless, instances of clinical multidrug-resistant M. genitalium infections are increasingly being documented in many countries [22,23], and here, we observed that this is the emerging problem in Croatia as well. Alternative therapies such as minocycline, pristinamycin and chloramphenicol are considered third-line options [24]; however, accessing these drugs is challenging in Croatia and other European countries.…”
Section: Discussionsupporting
confidence: 56%
“…While fluoroquinolone resistance may not always lead to treatment failure, certain patients may still respond favourably to moxifloxacin treatment. Nevertheless, instances of clinical multidrug-resistant M. genitalium infections are increasingly being documented in many countries [22,23], and here, we observed that this is the emerging problem in Croatia as well. Alternative therapies such as minocycline, pristinamycin and chloramphenicol are considered third-line options [24]; however, accessing these drugs is challenging in Croatia and other European countries.…”
Section: Discussionsupporting
confidence: 56%